The reform of the internal affairs bodies is one of the main priorities of the Democratization of the Judicial and Legal system - Bekhzod Nurboyevich Rashidov (Research Parks Publishers, 2021)
This article reveals the main points of the reform of the system of internal affairs bodies initiated by the President of the Republic of Uzbekistan in recent years. Special attention is paid to the further steps in the modernization of the internal affairs bodies determined by the Head of State